2006
DOI: 10.1152/advan.00013.2006
|View full text |Cite
|
Sign up to set email alerts
|

Peer instruction enhanced student performance on qualitative problem-solving questions

Abstract: We tested the hypothesis that peer instruction enhances student performance on qualitative problem-solving questions. To test this hypothesis, qualitative problems were included in a peer instruction format during our Physiology course. Each class of 90 min was divided into four to six short segments of 15 to 20 min each. Each short segment was followed by a qualitative problem-solving scenario that could be answered with a multiple-choice quiz. All students were allowed 1 min to think and to record their answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
65
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 15 publications
(26 reference statements)
8
65
2
1
Order By: Relevance
“…The reasons most often advanced for not including these collaborative activities include concerns that less-prepared students will be "carried" by the more industrious ones or that they will defer to their higher-performing classmates. However, students reported that every group member "pulled their weight" and that the level of discussion and their involvement were high during collaborative group testing as well as peer instruction activities (4,8). Furthermore, current evidence suggests that students feel a responsibility for the group's success and that group members tend to ensure that everyone is doing their share (11).…”
mentioning
confidence: 93%
“…The reasons most often advanced for not including these collaborative activities include concerns that less-prepared students will be "carried" by the more industrious ones or that they will defer to their higher-performing classmates. However, students reported that every group member "pulled their weight" and that the level of discussion and their involvement were high during collaborative group testing as well as peer instruction activities (4,8). Furthermore, current evidence suggests that students feel a responsibility for the group's success and that group members tend to ensure that everyone is doing their share (11).…”
mentioning
confidence: 93%
“…We also learn by talking in the classroom (1,4,5,16,30). In fact, discussion enhances student understanding even when none of the students initially know the correct answer (9,24). Furthermore, discussion enriches the learning experience by increasing engagement and interest while promoting thinking about what is understood and what remains to be understood (27).…”
mentioning
confidence: 99%
“…For example, active learning strategies, including peer instruction (5,17,26,27,39), collaborative testing (4,34,38), construction of physical models (19), and playing educational games (20,33,35,41), have been shown to enhance intellectual intelligence (21,24,31). Furthermore, active learning strategies, such as model construction and manipulation, encourage critical thinking, problem solving, collaboration, and interactive learning (19,32,36).…”
mentioning
confidence: 99%